2018
DOI: 10.3892/ijo.2018.4374
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-18a inhibits cell growth and induces apoptosis in osteosarcoma by targeting MED27

Abstract: Osteosarcoma (OS) is a common malignant primary bone tumor and patients with OS are known to have a poor response to chemotherapy. MicroRNAs (miRNAs or miRs) are small non-coding RNA molecules (approximately 22 nucleotides in length) and they have recently become a topic for research as regards their role in cancer therapeutics. Previous studies have reported miR‑18a expression in patients with OS is significantly decreased compared with that in normal adjacent tissue. miR‑18a belongs to the miR‑17‑92 cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(56 reference statements)
1
14
0
1
Order By: Relevance
“…Thus, compared with the direct transcriptional regulation approved in our study, such indirect regulation might still need further exploration. Besides, CRSP8 was recently reported to be reversely regulated by miR-18a, which belongs to the miR-17-92 cluster, as its direct target in osteosarcoma [44], implying the possibility that miR-18a might similarly regulate CRSP8 in thyroid cancer cells. Nevertheless, considering earlier reports that all members of miR-17-92 cluster except miR-17-3p were overexpressed and partial play oncogenic function in ATC [45], the hypothesis mentioned above seems not valid.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compared with the direct transcriptional regulation approved in our study, such indirect regulation might still need further exploration. Besides, CRSP8 was recently reported to be reversely regulated by miR-18a, which belongs to the miR-17-92 cluster, as its direct target in osteosarcoma [44], implying the possibility that miR-18a might similarly regulate CRSP8 in thyroid cancer cells. Nevertheless, considering earlier reports that all members of miR-17-92 cluster except miR-17-3p were overexpressed and partial play oncogenic function in ATC [45], the hypothesis mentioned above seems not valid.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported miR‐18a to have a proangiogenic function during tumor angiogenesis . miR‐18a can inhibit cell growth and induces apoptosis through targeting MED27 gene and inhibiting its expression, but some research showed miR‐18a plays a key role in tumor suppression through targeting TBPL1 gene . miR‐223 can promote cancer cell invasion and metastasis by downregulating p120, thereby reducing intercellular adhesion, promoting RhoA activity, and activating β‐catenin signaling .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short non-coding RNAs with a length of ~ 22 nt, which act as vital regulators in biological processes, such as cell proliferation and differentiation [12]. miRNA has been reported to be involved in osteoporosis by binding the 3'-'UTR of their target mRNA.…”
Section: Introductionmentioning
confidence: 99%